Chest Pain in Women: Gender- and Sex-based Differences in the Presentation and Diagnosis of Heart Disease - Mariem A Sawan; Rebecca S Steinberg; Michael N Sayegh; Christian Devlin; Omid Behbahani-Nejad; Nanette K Wenger (US Cardiology Review)
Ischemic heart disease is a major cause of morbidity and mortality in the US, affecting both men and women significantly. The presentation of chest pain is largely similar in female and male patients, but additional non-chest pain symptoms can confound timely diagnosis in women. Management, diagnostic evaluation, and clinical outcomes for patients admitted with chest pain differ significantly between men and women, and understanding of these discrepancies is limited. The objective of this review is to familiarize readers with gender- and sex-specific differences in the presentation, diagnosis, and management of chest pain.